Pemanfaatan Big Data oleh Petani Milenial Kota Bandung: Tinjauan Teori Difusi Inovasi - Solihin, Olih; Siregar, ballian; Aminah, Ratih Siti; Abdullah, Ahmad Zakki (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
Utilization of Big Data in agricultural practices has become a crucial topic, particularly for millennial farmers in Bandung City. Modern agriculture requires swift and precise access to information to enhance efficiency and productivity. This research aims to explore how the utilization of Big Data influences millennial agricultural practices in Bandung City and to provide recommendations for improving its usage in the agricultural sector. The study employs a qualitative approach with in-depth interviews and participatory observation of active millennial farmers in Bandung City. The analysis reveals that the adoption of Big Data, viewed through the lens of Innovation Diffusion Theory, strengthens communication among farmers, facilitates the formation of cooperatives based on available data, expedites decision-making processes, and aids in optimizing resource utilization. Strengthening technological infrastructure, enhancing training and education, providing financial support, fostering partnerships, and advocating supportive policies can enhance the utilization of Big Data, thus positively impacting millennial agriculture in Bandung City.